Radar Observations of the Arid Meteor Shower Outburst from Comet 15P/Finlay - Diego Janches; Juan Sebastian Bruzzone; Robert J. Weryk; Jose Luis Hormaechea; Claudio Brunini (The Planetary Science Journal, 2023)
We report on observations of the anticipated, first time occurrence, Arid meteor shower produced by comet 15P/Finlay. This comet, which has not been noteworthy for over a century, produced two major outbursts of activity during perihelion passage between 2014 December and 2015 January. Various authors predicted that Earth would cross the resulting ejecta on 2021 October 6–7 UT with a radiant in the constellation Ara, optimally placed to be observed from the Southern Hemisphere. We observed two outbursts using the Southern Argentina Agile Meteor Radar-Orbital System: one on 2021 September 29 and a second more dominant peak on 2021 October 7, centered around α = 260.°34, δ = −57.°63 and α = 255.°01, δ = −48.°47, respectively. The 6.5 mag limit flux and zenithal hourly rates were 0.073 meteors km ^−2 hr ^−1 and 491 hr ^−1 , respectively. The time of occurrence of the two detected peaks are in good agreement with predictions of this shower reported by several authors, confirming the validity of the models used for the predictions.